ANALISIS PERHITUNGAN HARGA POKOK SEWA KAMAR DENGAN ACTIVITY BASED COSTING SYSTEM (ABC SYSTEM) (Studi pada Guest House Hasanah Buring Kota Malang Tahun 2016) - Nivo Haneda; Devi Farah Azizah (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
More accurate determining of cost is important as a basis for decision-making for the management of service company. During this time Hasanah Buring Guest House isn’t use special method in determining the rate of rent room. Rate of rent room is determined by the owner and manager by doing simple calculations, that way can make distorted calculations. One method that can be used to calculate cost of the rent room is by using Activity Based Costing System, so that researchers interested in making the research under the title